Review of "A Grammatical Outline of Gùrdùŋ/Gùrùntùm", by Andrew Haruna - (:unkn) unknown (My University, 2007)
With his Grammatical outline of Gùrdùŋ, Andrew Haruna (A.H.) has published the first grammar of a South-Bauchi Chadic West-B language. This type of work, concerning a minority language spoken in Bauchi State (Northern Nigeria) and dominated by Hausa, is highly welcome and should be emulated. Despite serious shortcomings, A. H.'s work is worth commending. It provides a good quantity of data, consistently transcribed and reasonably well analysed. The author's aims is to provide a description of the essential aspects of Gùrdùŋ (G.), focusing on the description of the verbal and nominal systems in the present-day form of the language.
Keywords: African Research